Differentiate z = e^(3y^2+5) with respect to y. (Hint: use chain rule.)

We can find dz/dy using chain rule dz/dy=dz/du x du/dy (1) by defining u=3y^2+5 (since the exponent of e is a function of y we call this function u) and rewrite z=e^u. Then, we find dz/du=e^u (2) and du/dy=6y (3). Now we can substitute (2) and (3) into (1) to find dz/dy=e^u 6y =6y e^(3y^2+5), where in the last line we substitute u=3y^2+5. (Ensure that you give your answer in terms of y.)

Answered by Sophie H. Maths tutor

2583 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Derive from the standard quadratic equation, the form of the quadratic solution


How do I find the equation of a tangent to a given point on a curve?


Find the integral of 4/(1-x^2) dx:


Factorise f(x)=3x^3+8x^2-20x-16 completely


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences